Passing On The Faith transforming traditions for the next generation of Jews, Christians, and Muslims - Heft, James (New York Fordham University Press, 2006)
From the beginning, the Abrahamic faiths--Judaism, Christianity, and Islam--have stressed the importance of transmitting religious identity from one generation to the next. Today, that sustaining mission has never been more challenged. Will young peopl
Keywords: Christianity. Islam. Judaism. Monotheism